Testing the effectiveness of protocols for removal of common conservation treatments for radiocarbon dating - Brock, Fiona; Dee, Michael; Hughes, Andrew; Snoeck, Christophe; Staff, Richard; Ramsey, Christopher B. (University of Arizona / Cambridge University Press, 2017)
To achieve a reliable radiocarbon date for an object, any contamination that may be of a different age must be removed prior to dating. Samples that have been conserved with treatments such as adhesives, varnishes or consolidants can pose a particular challenge to radiocarbon dating. At the Oxford Radiocarbon Accelerator Unit (ORAU), common examples of such substances encountered include shellac, the acrylic polymers Paraloid B-67 and B-72, and vinyl acetate-derived polymers (e.g. ‘PVA’). Here, a non-carbon containing absorbent substrate called Chromosorb® was deliberately contaminated with a range of varieties or brands of these conservation treatments, as well as two cellulose nitrate lacquers. A selection of chemical pretreatments was tested for their efficiency at removing them. While the varieties of shellac and Paraloid tested were completely removed with some treatments (water/methanol and acetone/methanol/chloroform sequential washes, respectively), no method was found that was capable of completely removing any of the vinyl acetate-derived materials or the cellulose nitrate lacquers. While Chromosorb is not an exact analogue of archaeological wood or bone, for example, this study suggests that it may be possible to remove aged shellac and Paraloid from archaeological specimens with standard organic-solvent-acid-base-acid pretreatments, but it may be significantly more difficult to remove vinyl acetate-derived polymers and cellulose nitrate lacquers sufficiently to provide reliable radiocarbon dates. The four categories of conservation treatment studied demonstrate characteristic FTIR spectra, while highlighting subtle chemical and molecular differences between different varieties of shellac, Paraloid and cellulose nitrate lacquers, and significant differences between the vinyl acetate derivatives.